Teaching reading comprehension in english in a distance web-based course: new roles for teachers (2010)
Distance web-based learning is a popular strategy in ELT teaching in Colombia. Despite of the growth of experiences, there are very few studies regarding teachers’ participation in these courses. This paper reports preliminary findings of an on-going study aiming at exploring the roles that a teacher plays in an EFL reading comprehension distance web-based course. Data analysis suggests that teachers play new roles solving technical problems, providing immediate feedback, interacting with students in a non traditional way, providing time management advice, and acting as a constant motivator. The authors conclude that EFL teachers require training for this new teaching roles and the analysis of webbased distance learning environments as an option under permanent construction that requires their active participation. El aprendizaje a distancia con apoyo de la red se ha convertido en una estrategia popular en la enseñanza del inglés en Colombia. A pesar de ser una experiencia en crecimiento, hay pocos estudios relacionados con la participación del docente en estos cursos. Este artículo presenta los hallazgos preliminares de un estudio que busca explorar los roles que un docente de inglés como lengua extranjera tiene en un curso de competencia lectora en un programa a distancia basado en la red. El análisis de los datos sugiere que los docentes enfrentan aspectos como la resolución de problemas técnicos, la provisión inmediata de retroalimentación, la interacción con los estudiantes en una forma no tradicional, la asesoría en el manejo del tiempo y el ser un motivador constante. Los autores concluyen que los docentes de inglés como lengua extranjera requieren formación para estos nuevos roles y el análisis de ambientes de aprendizaje a distancia como una opción en permanente construcción que demanda su participación activa.